Handbook of Magnetism and Advanced Magnetic Materials 2007
DOI: 10.1002/9780470022184.hmm423
|View full text |Cite
|
Sign up to set email alerts
|

Hard Magnetic Films

Abstract: Hard magnetic films, showing high magnetocrystalline anisotropy, have been attracting much attention recently for application to magnetic devices since the critical grain size for superparamagnetic limit can be reduced to the nanometer scale. In this chapter, the fabrication techniques and the magnetic properties of hard magnetic films are reviewed. Firstly, the fundamental phenomena and models which are important for the understanding of hard magnetic properties in thin films are described. Secondly, the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Shima and Takanashi have also reported a tendency for the coercivity of a nanoscale magnetic material to reach a maximum and then decrease with increasing particle size. They claimed that the maximum of the coercivity may be related to the cooperative rotation of magnetic moments [16]. Besides this possibility, previous work has also revealed that the fcc phases in binary Cu-Fe and Fe-Co alloys exhibit paramagnetism.…”
Section: Magnetization Measurementsmentioning
confidence: 98%
“…Shima and Takanashi have also reported a tendency for the coercivity of a nanoscale magnetic material to reach a maximum and then decrease with increasing particle size. They claimed that the maximum of the coercivity may be related to the cooperative rotation of magnetic moments [16]. Besides this possibility, previous work has also revealed that the fcc phases in binary Cu-Fe and Fe-Co alloys exhibit paramagnetism.…”
Section: Magnetization Measurementsmentioning
confidence: 98%
“…For spintronic applications such as spin transfer torque magnetoresistance random access memory (STT-MRAM), many materials have been researched and developed focusing on their magnetic properties. 1,2) Recently, materials with high perpendicular magnetic anisotropy (PMA) have become especially popular for spintronic devices, [3][4][5][6][7][8][9] because these materials lead to the reduction in critical current density and a high thermal stability factor in STT-MRAM devices. Among these materials, Mn-based ordered alloys with tetragonal crystal structures are strongly attractive materials suitable for fulfilling these requirements owing to their high uniaxial magnetocrystalline anisotropy (K u ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several preparation techniques to meet user's need. Some of them for UHV systems are magnetron sputtering deposition, molecular beam epitaxial and e-beam evaporation, and pulse laser deposition [7]. Due to the advantages of the preparation techniques, thin films started being used widely in technological applications such as optics [2], optoelectronics [3], electronics [4], magnetic applications [5], and sensors [6].…”
Section: Introductionmentioning
confidence: 99%